Activist-Appointed Directors. (27th June 2022) - Kang, Jun-Koo; Kim, Hyemin; Kim, Jungmin; Low, Angie
Abstract: We examine the value impact of independent directors nominated by activists (Activist IDs). Firms appointing Activist IDs experience larger value increases than firms appointing other directors, particularly when Activist IDs have private firm experience and when their nominators remain as shareholders. This value increase persists over a long period and is greater than that of activism events without director appointments. The increase is also higher among firms with greater monitoring needs and entrenched boards. Moreover, the appointments of Activist IDs are greeted more positively by the market, and Activist IDs obtain more favorable shareholder votes and additional future directorships.